Tapis Social Entrepreneurship Orientation as a Cultural Preservation Instrument in Lampung - Herlin Nurristania Aulia; Junaidi; Damar Wibisono (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2025)
Tapis cloth, which is a traditional textile work originating from the Lampung Region, is important to preserve. National, Regional Governments, and also MSMEs are important aspects in contributing to this preservation. Social entrepreneurship is one of the efforts in cultural preservation. This study aims to reveal the orientation of social entrepreneurship in the Jejama Kham filter business in Katon State Village, Pesawaran, through a qualitative method with a literature review approach supported by field data. This research uses the theory of innovation by Schumpeter which states that economic progress and growth can be achieved with innovations made by an entrepreneur to create a change. The results of the study show that Jejama Kham's filter business is not only oriented to material profits but also fully tries to preserve Lampung filter fabric. Not only that, Jejama Kham's filter business is also in line with Schumpeter's innovation theory because in practice Jejama Kham applies many innovations in a series of stages of filter fabric production.